2004
DOI: 10.2337/diabetes.53.5.1215
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Insulin Sensitivity and Sphingomyelin Signaling Pathway in Human Skeletal Muscle

Abstract: In vitro studies revealed that insulin resistance might be associated with the intracellular formation of ceramide, the second messenger in the sphingomyelin signaling pathway. The aim of the present study was to examine the content and composition of fatty acids in ceramide and sphingomyelin in human muscle and to evaluate their relationships with insulin sensitivity. The study was conducted on 27 male subjects with normal glucose tolerance. Euglycemic-hyperinsulinemic clamps and biopsies of vastus lateralis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
180
6
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(210 citation statements)
references
References 53 publications
(56 reference statements)
19
180
6
4
Order By: Relevance
“…Effect of insulin on muscle ceramide content In the present study, muscle ceramide content was not influenced by stimulation with low or high insulin levels during the clamp, which is consistent with prior observations showing no effect of insulin on muscle ceramide content in human skeletal muscle [11,15,16]. Muscle ceramides are generated primarily through de novo synthesis from palmitate and serine, or through the breakdown of sphingomyelin in the membranes [22,28,29].…”
Section: Basalsupporting
confidence: 91%
See 4 more Smart Citations
“…Effect of insulin on muscle ceramide content In the present study, muscle ceramide content was not influenced by stimulation with low or high insulin levels during the clamp, which is consistent with prior observations showing no effect of insulin on muscle ceramide content in human skeletal muscle [11,15,16]. Muscle ceramides are generated primarily through de novo synthesis from palmitate and serine, or through the breakdown of sphingomyelin in the membranes [22,28,29].…”
Section: Basalsupporting
confidence: 91%
“…However, in contrast, we observed similar muscle ceramide content in endurancetrained compared with untrained normal young men [14]. Studies using lipid infusion to decrease insulin sensitivity under a euglycaemic-hyperinsulinaemic clamp have also produced conflicting results: one group observed no change in muscle ceramide levels after 6 h [15], whereas another group found that ceramide levels were increased after 4h [16]. Overall, it is not clear from the literature whether muscle ceramide content plays a major role in skeletal muscle insulin sensitivity.…”
Section: Introductioncontrasting
confidence: 43%
See 3 more Smart Citations